2021
DOI: 10.1002/eji.202048901
|View full text |Cite
|
Sign up to set email alerts
|

UNC93B1 curbs cytosolic DNA signaling by promoting STING degradation

Abstract: UNC93B1 is a trafficking chaperone of endosomal Toll‐like receptors (TLRs) and plays an essential role in the TLR‐mediated innate signaling. However, whether it is also involved in other innate immune sensing or cellular pathways remains largely unexplored. Here we investigated the role of UNC93B1 in cytosolic DNA‐triggered cGAS‐STING signaling in mouse and human cell lines. We showed that while UNC93B1 deficiency blunts the signal transduction by TLR3, it augments innate immune responses to cytosolic DNA stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…During our generation of Unc93b1 -/--deficient (Unc93b1 −/− ) mice, a recent in vitro study showed that UNC93B1 deficiency augments innate immune responses to cytosolic DNA stimulation and DNA virus infection via stabilizing STING and potentiating the cGAS-STING signaling pathway, 23 which is consistent with our findings. In addition, our in vivo study demonstrates that Unc93b1 −/− mice are more resistant to HSV-1 infection with higher IFN-β production and IFN-β, ISG54, and ISG56 transcriptions than WT littermates, corroborating our conclusion.…”
supporting
confidence: 91%
“…During our generation of Unc93b1 -/--deficient (Unc93b1 −/− ) mice, a recent in vitro study showed that UNC93B1 deficiency augments innate immune responses to cytosolic DNA stimulation and DNA virus infection via stabilizing STING and potentiating the cGAS-STING signaling pathway, 23 which is consistent with our findings. In addition, our in vivo study demonstrates that Unc93b1 −/− mice are more resistant to HSV-1 infection with higher IFN-β production and IFN-β, ISG54, and ISG56 transcriptions than WT littermates, corroborating our conclusion.…”
supporting
confidence: 91%
“…TLR2, 7, 9, and other subtypes also contribute to viral recognition (53, 54) (Figure 2). UNC93B1 is a multi-transmembrane protein that plays a crucial role in necleic-acid-sensing TLR signaling (55). Studies have shown that the UNC93B1 regulates the TLR7/9 signaling pathway by transferring TLR7 and 9 to endolysosomes (56).…”
Section: Primary Immune Response In Hsvementioning
confidence: 99%
“…Many endosomal interactors with STING1 have been identified at the late activation stage in RAW264.7 cells, providing an integrated mechanism to control STING1 trafficking ( 43 ). Unc-93 homolog B1, TLR signaling regulator (UNC93B1) is a chaperone of endosomal toll-like receptors (TLRs) and acts as a repressor of STING1 activation by anchoring STING1 in the endosomes of human and mouse fibroblasts ( 67 ). Endosomal TLRs play a role in the activation of B cells in the context of autoimmune diseases ( 68 ).…”
Section: Roles Of Sting1 In Organellesmentioning
confidence: 99%